Successful Management of Infectious Crystalline Keratopathy with Intrastromal Antibiotic Injections - Luis Martinez-Velazquez; Kevin K. Ma; Neal S. Patel; Zhonghui Katie Luo (Case Reports in Ophthalmological Medicine)
Purpose. To report the successful treatment of a case of presumed infectious crystalline keratopathy with repeated intrastromal antibiotic injections in a cornea graft in the setting of severe ocular graft-vs.-host-disease (GVHD). Observations. A 62-year-old man with a history of ocular GVHD and tectonic penetrating keratoplasty (PK) for corneal melt from herpes zoster keratopathy developed presumed infectious crystalline keratopathy (ICK) in the corneal graft. Given the patient’s complicated ocular history, chronic immunosuppression and new cardiac comorbidities, a therapeutic PK would most likely fail. Efforts were then directed to rescue the graft with minimally invasive approaches. Two separate intrastromal injections of cefuroxime and moxifloxacin successfully treated his ICK. Conclusions and Importance. This case supports a role for repeated intrastromal antibiotic injections in patients with ICK refractory to topical antibiotic therapy, which might eliminate the need for therapeutic PK and preserve vision.